Pengaruh Penerapan Balanced Scorecard terhadap Kinerja Manajemen di BPRS PNM Mentari Garut - Susanti Laelasari; Adi Indradi Wazdi; Yudi Guntara; Anggit Suryopratomo (Ma'soem University, 2023)
This research is motivated by the weakness of the company's performance measurement system that focuses on financial aspects and ignores non-financial performance, so a performance measurement model is made using the balanced scorecard. This study aims to determine how the effect of the balanced scorecard on management performance in BPRS PNM Mentari Garut. The object of this research is to measure management performance. This type of research is quantitative associative. Data collection techniques in the form of observation, interviews, literature study and questionnaires. While the population is all employees, amounting to 42 people. The results showed that there was no influence of the financial perspective on management performance with the results of the t-test value tcount < ttable (1,933 < 2,021), there was a significant influence between the customer perspective on management performance and the results of the t test value tcount > ttable (3.182 > 2.021), there is a significant effect between the internal business process perspective on management performance with the results of the t-test value tcount > ttable (3,800 > 2,021), there is a significant influence between the learning and growth perspective on management performance with the t test results tcount > ttable (4,474 > 2,021), Simultaneously the Balanced Scorecard has a significant effect on management performance, it can be seen in the F test that the value of Fcount > Ftable (5.835 > 2.63).